(untitled) (Bangladesh Journal of Pharmacology, 2020)
The present study evaluates the antiviral activity of banana lectin (BanLec) against herpes simplex virus type 1 and 2 (HSV-1 and HSV-2). Lectin was isolated from the ripen pulp of bananas (Musa paradisiaca). The study showed that lectin exhibited hemagglutination activity towards human erythrocytes A, B, AB and O group. The molecular weight of BanLec using SDS gel-electrophoresis was found to be 14,000-30,000 Da. Cytotoxicity of BanLec on the Vero cell lines showed an inhibitory concentration of 172.7 µg/mL. BanLec was virucidal and showed no cytotoxicity at the concentration tested. The lectin showed a dose-dependent antiviral activities, inhibiting HSV-1 by 16.0 µg/mL with selectivity index 10.8 and HSV-2 inhibition by 67.7 µg/mL with selectivity index 2.6. These results corroborate that BanLec could be a rich source of potential antiviral compound for HSV-1 when compared to HSV-2. Video Clip of Methodology: Hemaglutination test: 11 min 29 sec: Click to watch